(untitled) (Journal of actual problems of jurisprudence, 2022)
Information legal relations today are quite a familiar phenomenon that millions of people enter into every day and everywhere. The range of subjects, boundaries, volumes and spheres of interaction is constantly expanding and attempts at their legal regulation often do not have time. At the same time, the development of information legislation has progressed far enough today, as evidenced by both international and national law. However, from a theoretical point of view, information law is not stable. Theorists in this field have not come to the solution of many basic issues, including the subject of regulation, the range of subjects and their legal status in certain situations, the time of the emergence and termination of legal personality and many other aspects, including the concept of Information law as a branch of law. The presented article attempts to analyze the concept and structure of information legal relations from the point of view of modern aspects of the development of information exchange. Special attention is paid to the specifics of the legal status of subjects of information legal relations, which is a necessary condition for effective legal regulation of information exchange and ensuring its legality and intensity. Keywords: information, information legal relations, information legal personality, subject of information legal relations, information law, blogger.